Cover Feature: Sustainable Catalytic Synthesis of Diethyl Carbonate (ChemSusChem 3/2021). Issue 3 (19th January 2021) - Putro, Wahyu S.; Ikeda, Akira; Shigeyasu, Shinji; Hamura, Satoshi; Matsumoto, Seiji; Lee, Vladimir Ya.; Choi, Jun‐Chul; Fukaya, Norihisa
Abstract : The Cover Feature shows the new synthesis of diethyl carbonate from CO2 and alkoxysilanes using a zirconium catalyst. The disiloxane byproduct can be reverted to alkoxysilanes using ethanol and molecular sieves as dehydrating agent, which offers a new sustainable approach toward the development of waste‐free synthesis of diethyl carbonate. More information can be found in the Communication by W. S. Putro et al .